Kemampuan Representasi Matematis Siswa SMP pada Materi Kekongruenan dan Kesebangunan - Herdiman, Indri; Jayanti, Koentri; Pertiwi, Kholifia Ayuning; Naila N., Resti (Universitas Hamzanwadi, 2018)
The ability of the mathematical representation is the ability to create a model of a problem into a new form of verbal, text, tables, or graphs. The research is a qualitative descriptive study aimed to systematically describe the capabilities of mathematical representation. Data collection techniques in this study conducted using tests such as about the description, the test is given to students of class IX in one of the Junior High School in the city of Cimahi with 37 students. The results showed that the ability of the mathematical representation of students on the material for the indicator congruence and similarity of words or text are at less qualification with the percentage of students average score of 43%. Indicators visual representation including sufficient qualification with the percentage of students average score of 60%. On the indicator equations or mathematical expressions including the qualification is very less with the average percentage score of 34.75%. Difficulties faced by students predominantly found in Question 2b, 4b with the kind of test containing indicator words or text and Question 4c with indicators equations or mathematical expressions.